Providing Spiritual Dhikr Therapy to Patients with Sensory Perception Disorders and Auditory Hallucinations - Adista Nur Alifa; Enggal Hadi Kurniyawan; Erti Ikhtiarini Dewi; Amalia Kusumaningsih (Health and Technology Journal (HTechJ), 2025)
Hallucinations could cause someone to be unable to distinguish between what was real and what was merely an illusion. During hallucinations, the client could react with suspicion, fear, curiosity, insecurity, anxiety, and confusion. In this case, Mr. H experienced auditory hallucinations in the form of male whispers. Spiritual dhikr therapy could be used as an approach to healing mental illness, emphasizing inner strength. This study aimed to apply spiritual dhikr therapy to patients with sensory perception disorders: auditory hallucinations. The method used was a case study on a patient with hallucinations, with spiritual dhikr therapy intervention provided for 7 days to the patient. The therapy included reciting the phrase "Alhamdulillah" 33 times, "Subhanallah" 33 times, "Astaghfirullah" 33 times, and "Allahu Akbar" 33 times over 10-15 minutes. The client underwent hallucination management intervention and was given spiritual dhikr therapy. After being conducted for 7 days, the client experienced a decrease in the level of hallucinations and an improvement in hallucination control. Improvement in hallucination control could be achieved by providing continuous hallucination management and spiritual dhikr therapy, enabling the client to awaken their will and belief and understand the techniques being taught. Conclusion: The application of spiritual dhikr therapy could yield positive results and serve as an effective non-pharmacological therapy for clients with auditory hallucinations or schizoaffective disorders